(untitled) (Bangladesh Journal of Botany, 2015)
Rice plants absorb substantial amount of arsenic when grown in rice field soil containing 3.21 mg/kg arsenic and irrigated with contaminated groundwater from a shallow tube-well having 476 ± 3 ?g arsenic/l at Sonargaon, Bangladesh. It is revealed that highest total arsenic accumulation occurred in roots (5.790 ± 0.337 mg/kg) followed by shoots (3.766 ± 0.370 mg/kg) and brown-rice grains (2.552 ± 0.507 mg/kg). The concentration of total arsenic in rice grains was beyond permissible limit (1.00 mg/kg) for human consumption. At the time of harvest 4.90 ± 1.11 - 8.27 ± 1.35 mg As/kg soil remained in the rice field soil. However, majority of the soil arsenic is washed out by rain and flood water leaving more than 3.00 mg As/kg soil after flood period which along with high level of As contaminated groundwater for irrigation, elevated the level (up to 8.27 ± 1.35 mg As/kg soil) beyond permissible limit of e.g. in USA it is 5 mg/kg soils for agriculture use. To keep the environment clean, surface water for irrigation has been suggested. DOI: http://dx.doi.org/10.3329/bjb.v44i1.22728 Bangladesh J. Bot. 44(1): 85-89, 2015 (March)